Comparison of the hypothetical 57Co brachytherapy source with the 192Ir source - Toossi, Mohammad Taghi Bahreyni; Ghorbani, Mahdi; Rostami, Atefeh; Khosroabadi, Mohsen; Khademi, Sara; Knaup, Courtney (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : The 57 Co radioisotope has recently been proposed as a hypothetical brachytherapy source due to its high specific activity, appropriate half-life (272 days) and medium energy photons (114.17 keV on average). In this study, Task Group No. 43 dosimetric parameters were calculated and reported for a hypothetical 57 Co source. Material and methods : A hypothetical 57 Co source was simulated in MCNPX, consisting of an active cylinder with 3.5 mm length and 0.6 mm radius encapsulated in a stainless steel capsule. Three photon energies were utilized (136 keV [10.68%], 122 keV [85.60%], 14 keV [9.16%]) for the 57 Co source. Air kerma strength, dose rate constant, radial dose function, anisotropy function, and isodose curves for the source were calculated and compared to the corresponding data for a 192 Ir source. Results : The results are presented as tables and figures. Air kerma strength per 1 mCi activity for the 57 Co source was 0.46 cGyh–1 cm 2 mCi–1. The dose rate constant for the 57 Co source was determined to be 1.215 cGyh–1U–1. The radial dose function for the 57 Co source has an increasing trend due to multiple scattering of low energy photons. The anisotropy function for the 57 Co source at various distances from the source is more isotropic than the 192 Ir source. Conclusions : The 57 Co source has advantages over 192 Ir due to its lower energy photons, longer half-life, higher dose rate constant and more isotropic anisotropic function. However, the 192 Ir source has a higher initial air kerma strength and more uniform radial dose function. These properties make 57 Co a suitable source for use in brachytherapy applications.